THE INFLUENCE OF LIQUID VISCOSITY ON FALLING TIME BY FALLING BALL METHOD - Nur Azizah Lubis (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2018)
A study has been conducted to determine the influence of liquid viscosity on falling time using the falling ball method. The results showed that there was an effect of liquid viscosity on the fall time which can be seen from the oil viscosity value ( ) = 15.94 dyn s/cm2 which is greater than glycerin ( ) = 15.51 dyn s/cm2 and the coefficient of determination (R2) of oil and glycerin are 0.9958 and 0.9799, respectively. Temperature changes in oil are lower than glycerin. In oil, the initial temperature is 30.1 °C and the final temperature is 30.5 °C, while in glycerin, the initial temperature is 31.1 °C and the final temperature is 31.8 °C. This shows that the higher the viscosity of a liquid, the greater the time needed for the ball to fall. The more balls dropped, the more friction occurs so that the liquid temperature gets higher and the ball's falling speed gets faster and the liquid viscosity value gets lower. Keywords: Falling ball method, falling time, and liquid viscosity.